Options decimalization - Faith Chin; Corey Garriott (Bank of Canada, 2016)
We document the outcome of an options decimalization pilot on Canada's derivatives exchange. Decimalization improves measures of liquidity and price efficiency. The impact differs by the moneyness of an option and is greatest for out-of-the-money options. In contrast with equity studies, decimalization improved depth near the best prices and improved liquidity for larger trades. We conclude with advice on decimalizing options: options that benefit most have underlying volatility less than 40, underlying equity bid-ask spread less than 50 basis points, at least one trade a day, and a distribution of depth skewed toward marketable prices.
Keywords: G20; G14; L10; 330; Financial markets; Market structure and pricing; Financial system regulation and policies